Impact of brewery wastewater sludge on microbiological quality of agricultural soil - Christian, C. Ike; Prince, C. Odika; Peace, E. Okorie (Journal of Ecobiotechnology, 2019)
Impact of brewery wastewater sludge on microbiological quality of agricultural soil was studied using standard methods. Different concentrations of brewery wastewater sludge were added to soil sample collected from abandoned farm land to produce test soil samples A to C; and a control (without sludge). The samples were allowed to stay for 80 days with exposure to same environmental condition. Standard methods were deployed to isolate and group organisms from the soil samples. Important microbes such as Streptococcus sp., Klebsilla sp., Proteus sp., Vibrio sp., Shigella sp., Micrococcus sp., Pseudomonas sp., Enterobacter sp., Escherichia sp., and Bacillus sp amongst others were isolated. The isolated organisms and their loads were more on the test soil samples against the control. These could be indication of the impact of the brewery sludge on the soil. Organisms isolated and grouped have one or more beneficial role to play with relevance to agricultural soil. This study has revealed the impact of brewery wastewater sludge on microbiological quality of agricultural soil.